PENGARUH KOMPETENSI, KOMUNIKASI, SARANA PRASARANA DANPELATIHAN TERHADAP EFEKTIVITAS KERJA PEGAWAI DI KANTOR WILAYAH DJP SUMATERA UTARA I - Mildan Setiawan (Universitas Islam Sumatera Utara, 2020)
The formulation of the problem in this study are: Is there an influence of competence on employee work effectiveness in the Regional Office of North Sumatra I DGT, is there any effect of communication on employee effectiveness, is there an influence of infrastructure on employee effectiveness, is there an effect of training on employee effectiveness, ?, Is there any influence of competence, communication, infrastructure and training on the effectiveness of employee work in the North Sumatra DJP Regional Office I? Research Objectives Are: Data analysis technique used is multiple linear regression analysis.The results showed that there was a significant effect between competence on employee work effectiveness, because according to the results of the analysis of t count t-table (1.893 1.67) at n = 57 with a significance level of 95%, there was a significant effect between communication on effectiveness employee work, because according to the results of t analysis t-table (1,911 1.67) at n = 57 with a significance level of 95%, there is a significant effect between infrastructure on employee work effectiveness, because according to the results of t analysis t -table (3,311 1.67) at n = 57 with a significance level of 95%, there was a significant effect between training on employee work effectiveness, because according to the results of the analysis of t count t-table (4.995 1.67) at n = 57 with a significance level of 95%, F-count value F table (91,610 2.56) together (multiple) there is a positive and significant effect of competence, communication, infrastructure and facilities on the work productivity of large employee it was 88.3%. Thus the hypothesis proposed is accepted.